Application of red pitaya powder as a natural food colourant in fruit pastille - Low Pinn Yee; Than Chin Ping; Lim Pek Kui; Chan Sook Wah (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2017)
Background: Confectionary products meet the important consumers’ need states of fun and enjoyment, especially among children. Synthetic colourant had been applied as a colouring agent in confectionery products for decades, however various adverse health effects have been reported after consumption. Hence, usage of natural colourant has increased enormously as it confers functional and nutraceutical benefits. Red pitaya, a common and popular fruit cultivated in South-east Asian countries. It is rich betacyanin content that gives the fruit a red-violet colour. Hence, red pitaya is a potential source of natural colorant as an alternative to the synthetic colorant.Objective: This research was aimed to produce fruit pastille with red pitaya powder applied as a natural colourant.Method: Production of red pitaya powder was achieved through spray drying process. Fruit pastille was prepared and subjected to antioxidant, stability and sensory analysis.Results: The Physicochemical study showed that pastille incorporated with red pitaya powder exhibited significantly (p<0.05) higher antioxidant properties than the blank pastille (control). An eight weeks storage stability study revealed that betacyanin content of pastille incorporated with pitaya powder remained stable for the first four weeks of storage. Besides, no significant change was observed in redness (a*) of pastille throughout the storage study. Sensory study was carried out to assess the consumer preference on pastille incorporated with pitaya powder and synthetic colourant. Colour attribute of pastille incorporated with red pitaya powder has gained significantly (p<0.05) higher liking that the one added with synthetic colour.Conclusion: Red pitaya powder could be a potential natural colourant for gummy confectionery.